Optimization Of Microwave-Assisted Transesterification Reaction Of Trimethylolpropane Triesters - Nur Atiqah Mohamad Aziz; Robiah Yunus; Umer Rashid; Zulkifly Abbas (Faculty of Engineering, Malikussaleh University, 2018)
Palm-based polyol ester answers the urgency for environmental preservation for biolubricant industry. In this study, microwave-assisted heating system was used to improve the transesterification reaction time of palm oil methyl ester (PME) and trimethylolpropane (TMP) and the results were compared with the conventional heating and pulsed-loop reactor methods. Response surface methodology (RSM) was applied to assess the optimum condition to produce high yield of TMP ester. Four factors; temperature (110-150 ˚C), pressure (10-30 mbar), molar ratio PME to TMP (3:1 – 5:1) and time (5-20 min) were selected to be optimized by using RSM. The interaction parameter of reaction temperature with the pressure was found to be the most significant amongst all of the reaction parameters. The highest TMP esters composition was obtained at 15 mbar, 0.6 wt% sodium methoxide, and molar ratio of 1:3.5 in 11 min was 63 wt%. The findings indicate that microwave-assisted reaction has successfully conducted at remarkably short time and at lower concentration of catalyst as compared to conventional methods.